The effectiveness of community engagement using M-Mama champions in improving awareness of obstetric danger signs, birth preparedness and complication readiness among pregnant women in Bahi, Dodoma: A cluster randomized pragmatic implementation trial. - Alex Sanga; Stephen Kibusi; James Tumaini Kengia (PLOS Global Public Health)
Background Maternal mortality remains a catastrophic condition for reproductive-age women in Tanzania. Inadequate ANC visits impair the efficiency of education programs for pregnant women on obstetric danger signs, birth preparedness and complication readiness, hence negatively influencing health behaviour and decision-making processes, contributing to maternal mortality. In this case, a complementary health education intervention for pregnant women in the community is necessary. M-MAMA Champions were introduced to determine their effectiveness in creating awareness of obstetric danger signs, birth preparedness complication readiness and their practice to complement the health system. Methods A parallel arms, cluster-randomized pragmatic implementation trial, whereby pregnant women were recruited from four clusters and randomised at a ratio of 1:1. M-MAMA Champions empowered pregnant women with obstetric danger signs, birth preparedness and complication readiness in addition to standard care. Difference-in-difference analysis determined the intervention's effect. Results The majority of 124 pregnant women recruited from intervention (N = 60) and control (N = 64) arms, were aged 16 to 19, 31.3% (n = 20) vs 20 to 24, 35.0% (n = 21) and had primary education 48.4% (n = 31) vs 51.7% (n = 31) in the control and intervention arms respectively. Awareness of Obstetric danger signs, birth preparedness complication readiness and their practice improved significantly by 64.2%, (P < 0.0001), 26.3%, (P = 0.00190 and 33.9%, (P = 0.0006) respectively. Conclusion M-MAMA Champions, the facilitators of women groups in community engagement are effective in improving awareness of obstetric danger signs, birth preparedness and complication readiness among pregnant women. It's, therefore worth an adoption for wider application. Trial registration NCT06325319 (Effect of Community Engagement Using M-Mama Champions), registered on 15th March 2024.